The Role Of Growth Temperature On The Indium Incorporation Process For Mocvd Growth Of InGaN/GaN Heterostructures - Yusof, Ahmad Sauffi; Hassan, Zainuriah; Hamady, Sidi; Ng, Sha Shiong; Ahmad, Mohd Anas; Way, Foong Lim; Fressengeas, Nicolas; Chevallier, Christyves (2020)
This work presents the effect of growth temperature on the evolution of indium incorporation and growth process of InGaN/GaN heterostructures grown using Taiyo Nippon Sanso Corporation (TNSC) metal organic chemical vapor deposition (MOCVD) SR4000-HT system. The InGaN/GaN heterostructures were epitaxially grown on 3.8 μm and 40 nm thick undoped-GaN (ud-GaN) and GaN nucleation layer respectively over a commercial 2” c-plane flat sapphire substrate (FSS). The InGaN layers were grown at different temperature setting ranging from 860°C to 820°C in a step of 20°C. The details structural, surface morphology and optical properties were investigated using X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), atomic force microscopy (AFM) and ultraviolet-visible (UV-Vis) spectrophotometer respectively.